PERLINDUNGAN HUKUM TERHADAP PEREMPUAN DAN ANAK DALAM KASUS KEKERASAN SEKSUAL (Studi Kasus Putusan Pengadilan Negeri Banda Aceh) - Rangga Setyadi; Muhammad Yamin; Ibnu Affan (LPPM YPITI, 2021)
Legal protection for women and children in cases of sexual violence in the city of Banda Aceh is regulated in various laws and regulations, namely national laws and regulations that apply specifically to the Aceh region, in the form of Qanun. Law enforcement against perpetrators of sexual violence against children in the city of Banda Aceh, there has been a dualism of law. The Aceh government, in addition to implementing the laws and regulations that apply nationally, also implements Qanun No. 6/2014 on Jinayat. Legal protection for women and children in cases of sexual violence at the Banda Aceh District Court is carried out through the imposition of the fairest verdicts against the defendants. In this case, the justice meant is justice for the victim. The verdict handed down by the Banda Aceh District Court against the defendant in the case of sexual violence against women (rape) is still too light, so that it has not brought justice to the victim, which is part of the form of legal protection for the victim.